(3agGQS hajGJ GdCYjGf aj CfHGA CHfGA GdReGfs - (3YHO GddWja jf YHO GdQMef Hf ESeGYjd GHf KfjGfs; (3GdSjO MLGRj s ((3YHO GdQGRb Hf GdedG eMeO GdMGL adjM GdHZOGOi s)
(3ChdgG (B:s
(3hHYO dbO TZafi MHkG JGQjN GHf NdcGf hdPG JhcdJ Ydi Gddg ai NOeI gPG GdJGQjN GdLdjd , hGSJNQLJ dg YOI agGQS s
(3BNQgG (B:s
(3jYbhH Hf OGhO GdegOi hGdYdhi Je s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B311 s
Keywords: (3GdJGQjNs